1981
DOI: 10.2307/1219951
|View full text |Cite
|
Sign up to set email alerts
|

VIRGULUS RAF. (1837), AN EARLIER NAME FOR LASALLEA GREENE (1903) (ASTERACEAE)

Abstract: Summary Virgulus Raf. (1837) is the earliest available name for those species of Aster L. with a basic chromosome number of x = 5, or derived x = 4. This name has priority over the recently reinstated Lasallea Greene (1903) which is additionally an orthographic variant of Lasallia Mérat (1821), a lichen. The necessary transfers are made from Aster to Virgulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Jones and Young, 1983). Utilizing the characteristics cited by Reveal and Keener (1981) to circumscribe Virgulus in a comparison with other Aster groups, I found that all except one (glandularity) also applied to Heleastrum (A. G. Jones, 1982). Two very striking shared traits are exhibited by the cypselas.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Jones and Young, 1983). Utilizing the characteristics cited by Reveal and Keener (1981) to circumscribe Virgulus in a comparison with other Aster groups, I found that all except one (glandularity) also applied to Heleastrum (A. G. Jones, 1982). Two very striking shared traits are exhibited by the cypselas.…”
mentioning
confidence: 95%
“…No previous chromosome count has been reported for this species which was placed, on the basis of morphological characteristics, in Virgulus, i.e., the x = 5 assemblage of Aster sensu lato [cf. A. G. Jones, 1980a;Jones and Young, 1983;Reveal and Keener, 1981;Semple and Brouillet, 1980a (as Lasallea)]. The NOR-chromosome is the largest of the genome, and the satellite is approximately half the size of the proximal end of the short arm.…”
mentioning
confidence: 99%
“…(b) Similar species and distinguishing characteristics-The literature prior to 1999 generally treats both Symphyotrichum ericoides and S. novae-angliae as members of the genus Aster (e.g., Britton and Brown 1913;Mackenzie 1926;Shinners 1941;Hill 1980; but see Semple and Brouillet 1980b;Reveal and Keener 1981). Chloroplast DNA evidence and gene sequence data (Noyes and Rieseberg 1999) demonstrate that Symphyotrichum is quite distinct from Aster.…”
mentioning
confidence: 99%
“…Semple & Brouillet. Adopting this generic concept but noting that Virgulus Raf. (1837) is the earliest generic name available for the group, Reveal and Keener (1981) made the pertinent nomenclatural transfers.…”
mentioning
confidence: 99%